Copyright, the Freedom of Expression and the Right to Information Exploring a Potential Public Interest Exception to Copyright in Europe - Mendis, Sunimal (Munich Intellectual Property Law Center - MIPLC, 2011)
With the advent of a global community, which draws its sustenance from the unfettered communication of ideas and expression, it is worth reflecting on the role of copyright law and considering whether the existing legal frameworks of copyright in Europe have the capacity to meet the changing needs of a new generation who have given a whole new meaning to the term ""creativity"" and to that of ""original expression."" This book considers the prevailing tension between the competing values of copyright, the freedom of expression, and the right to information. It also looks at the possibility of introducing a public interest exception to the copyright framework of the European Union as a means of resolving the existing discord, along with a comparative survey of the developments presently taking place in the jurisdictions of France, Germany, and the UK.